Improved photoactivity of TiO2–Fe2O3 nanocomposites for visible-light water splitting after phosphate bridging and its mechanism1. Issue 7 (21st February 2015) - Luan, Peng; Xie, Mingzheng; Fu, Xuedong; Qu, Yang; Sun, Xiaojun; Jing, Liqiang
<x xml:space="preserve">Abstract</x> The phosphate bridges built are favorable for charge transfer and separation, leading to a greatly-enhanced photoactivity for water splitting.